Diagnóstico del manejo de residuos de aparatos eléctricos y electrónicos para mejorar la gestión ambiental en la ciudad de Indiana. Loreto. 2022 - Rios Cahuaza, Candy Beatriz (2023)
The research is based on the inquiry about the management of WEEE waste from electrical and electronic equipment) as a proposal to improve environmental management in Indiana. Loreto. 2022. It is a descriptive, transectional work. A sample of 270 people who had some electrical or electronic device within the city was accessed. The results were: knowledge about electrical and electronic equipment waste is low and training on the subject would be convenient to be a start to improve their environmental management in the city of Indiana. Regarding the concept of WEEE, 74.1% do not know the subject and within electrical and electronic devices cell phones (35%), household appliances (18%), lighting devices (18.5%) and small devices (22%) prevail. Damaged or obsolete artifacts are deposited in their homes for up to 2 years, or they are disposed of by disposing of them in the city's municipal dump without taking into account their danger and they report that these artifacts are no longer reused (75.1%).